Influence of the ion size on the stability of the smectic phase of ionic liquid crystals - Cao, Wudi; Senthilkumar, Beeran; Causin, Valerio; Swamy, Vincent P.; Wang, Yanting; Saielli, Giacomo (Soft Matter, 2020)
The thermotropic phase behavior of ionic liquids and ionic liquid crystals based on novel N-alkyl-3-methylpyridinium halides, trihalides and dichloroiodates was experimentally studied by polarized optical spectroscopy (POM) and differential scanning calorimetry (DSC) as well as by molecular dynamics (MD) simulation. In the experiments, the existence and thermal range of stability of the smectic phase of these ionic liquid crystals are found to strongly depend on the volume ratio between the cation and anion, that is their relative size. Only compounds with a relatively large volume ratio of the cation to anion, i.e., those with longer cationic alkyl chains and monoatomic halide anions, have a stable smectic A phase. Both melting points and clearing points increase with such a ratio. The MD simulation results qualitatively agree very well with the experimental data and provide molecular details which can explain the experimentally observed phenomena: the stronger van der Waals interactions from the longer alkyl chains and the stronger electrostatic interactions from the smaller anions with a higher charge density increase the stability of both the crystal phase and the smectic phase; this also prevents the ionic layers from easily mixing with the hydrophobic regions, a mechanism that ultimately leads to a nanosegregated isotropic liquid phase.

Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2